2006
DOI: 10.1093/bja/ael073
|View full text |Cite
|
Sign up to set email alerts
|

Reflex pupillary dilatation in response to skin incision and alfentanil in children anaesthetized with sevoflurane: a more sensitive measure of noxious stimulation than the commonly used variables

Abstract: PD is a more sensitive measure of noxious stimulation than the commonly used variables of heart rate, arterial blood pressure and BIS in children anaesthetized with sevoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 17 publications
1
62
2
1
Order By: Relevance
“…They found that in response to a noxious stimulus, pupil dilatation was more sensitive and better correlated with opioid concentrations than heart rate, blood pressure and BIS monitoring. In a similar study performed in anaesthetised children, Constant et al 14 compared changes in pupil diameter with heart rate, blood pressure and BIS monitor variation in response to a skin incision on the lower limb. Similar to the adult data,16 these investigators were able to show that the change in pupil diameter had a greater effect size than BIS variation or haemodynamic markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that in response to a noxious stimulus, pupil dilatation was more sensitive and better correlated with opioid concentrations than heart rate, blood pressure and BIS monitoring. In a similar study performed in anaesthetised children, Constant et al 14 compared changes in pupil diameter with heart rate, blood pressure and BIS monitor variation in response to a skin incision on the lower limb. Similar to the adult data,16 these investigators were able to show that the change in pupil diameter had a greater effect size than BIS variation or haemodynamic markers.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of pupil dilatation can provide an index of nociceptive input via autonomic innervation of the iris muscles,14 15 while the extent of attenuation in this pupillary response during exposure to opioid analgesics can provide an index of pharmacological effect by reflecting the extent of occupancy of μ and κ opioid receptors in the central nervous system 16. Currently available handheld pupillometers are safe, well-tolerated by children, easy to use and modestly priced 17.…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating a tetanic stimulator with the pupillometer, we were able to accurately record a 10 second time course of pupil diameter changes in response to a standardized painful stimulus. PDR has been mostly studied on anesthetized patients and had been shown to be a useful tool to predict the level of analgesia [9]. PDR had also been used to check the level of an epidural analgesia during general anesthesia [29].…”
Section: Discussionmentioning
confidence: 99%
“…Constant et al . [9] confirm that PDR is an earlier and more sensitive response predictor of analgesia than the hemodynamic changes or the bispectral index (BIS) in children under general anesthesia. In the immediate postoperative period, the PDR is significantly correlated with the verbal rating scale [10].…”
Section: Introductionmentioning
confidence: 99%
“…The review will be limited to electroencephalogram (EEG)-derived devices. There are other ways to assess anaesthetic depth [12], but the EEG has been the focus of the overwhelming majority of research and publications in recent years. The review will approach the topic from a clinical perspective.…”
Section: Introductionmentioning
confidence: 99%